TO THE BIOLOGY OF THE SNOW TROUT IN THE UPPER REACH OF THE CHIRCHIK RIVER - Abdujalilov M.; Rakhmatova G.; Alimova A.; Yuldashov M. (Journal Park Publishing, 2023)
Males of the snow trout (Schizothorax curvifrons) in the upper reaches of the Chirchik River in Uzbekistan reach sexual maturity at the 2nd - 3rd year of life with a standard body length of 12 - 15 cm; females - in the 3rd - 4th year of life at 14 - 23 cm. Individual absolute fecundity is 6.6 - 71.5 thousand eggs. The coefficient of maturity of females before spawning was 5.48 - 17.5%. Yearlings reach an average standard length of 9.0 cm, two-year-olds - 13.9 cm, three-year-olds - 15.9 cm, four-year-olds - 21.7 cm, five-year-olds - 24.8 cm.
Keywords: Snowtrout, Schizothorax curvifrons, growth, maturation, fecundity, fish feeding, the Chirchik River, Uzbekistan.